SISTEM REKOMENDASI TEMPAT WISATA PADA INDUSTRY PARIWISATA DENGAN MENGGUNAKAN PRINCIPAL COMPONENT ANALYSIS - Nurul Adhiyansyah, - (2019)
The creative economy and the tourism sector are two things that are mutually influential and can work together if managed properly (Ooi, 2006). The concept of tourism activities can be defined by three factors, namely there must be something to see, something to do, and something to buy (Yoeti, 1985). Something to see related to attractions in tourist destinations, something to do related to tourist activities in tourist areas, while something to buy is associated with special souvenirs purchased in tourist areas as personal memorabilia \ tourists. When you want to introduce and travel in the Depok area, tourists will always be influenced by their emotions and feelings. Therefore, tourist attractions must consider this. One important aspect is introduction. Tourist attractions must now have many sales tasks ranging from attracting tourists, introducing facilities to attracting tourists. But tourist attractions in the Depok area are still very unpopular. In this research, the Principal Component Analysis method will be applied to identify the tourist's desire for tourist attractions to be visited as well as the use of information systems to help researcher determine what tourist attractions are in accordance with the wishes of tourists. The results of the research produced 5 of the most popular tourist attractions based on questionnaires and words that represented feelings when traveling. Based on the calculation of the linear regression equation, get the criteria for tourist attractions in accordance with the wishes of tourists